Recovery rates, default probabilities, and the credit cycle - Bruche, Max; González-Aguado, Carlos (Journal of Banking & Finance, 2010)
In recessions, the number of defaulting firms rises. On top of this, the average amount recovered on the bonds of defaulting firms tends to decrease. This paper proposes an econometric model in which this joint time-variation in default rates and recovery rate distributions is driven by an unobserved Markov chain, which we interpret as the “credit cycle”. This model is shown to fit better than models in which this joint time-variation is driven by observed macroeconomic variables. We use the model to quantitatively assess the importance of allowing for systematic time-variation in recovery rates, which is often ignored in risk management and pricing models.